IMPORTANCE OF WRITING REFLECTION ON LESSONS: IMPORTANCE OF WRITING REFLECTION ON LESSONS - Habibnazarova, Saiyra (Журнал иностранных языков и лингвистики, 2025)
A writing reflection is a personal, thoughtful analysis of your writing process and the work you’ve produced. It’s a way to look back on what you’ve written and examine your thoughts, decisions, and the challenges you encountered while writing. It’s not just about summarizing what you wrote, but rather exploring how you wrote it, what you learned from the experience, and how you can improve in the future.